INTEGRATED SCHOOL MANAGEMENT-CHARACTER EDUCATION AFFIRMATION: A CASE STUDY IN MUHAMMADIYAH WIROBRAJAN 3 ELEMENTARY SCHOOL YOGYAKARTA - Atika Atika; Zainal Arifin; Nora Saiva Jannana (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study aims to describe the integrated school management with PPK. The research was conducted at Muhammadiyah Wirobrajan 3 Elementary School in Yogyakarta City (Wibraga). This research is a qualitative approach. Data were collected through interviews, observations, and documentation. The results of this research are as follows: Firstly, the school management was integrated with the character education program at Wibraga, covering four functions; 1) The systemic-integrative planning by forming a development team for formulating PPK programs; 2) The organizing job description with three departments, the head of Curriculum and Teaching, ISMUBA and BHI, and Activities and Student Affairs; 3) The implementation of PPK programs was integrated through intra-curricular activities, the class based on co-curricular and extracurricular activities, Islamic and society life culture; 4) The controlling of PPK programs was realized in attitude books, school regulations, and external supervision with teachers, public relations, student parents, and local society.